Urban parks preferences for usability at Taman Tasik Seremban, Malaysia - Maulan, Suhardi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Urban Park is an important space in a particular city. The development of modern urban park can be traced back to Birkenhead Park in Liverpool, which was designed by Joseph Paxton in 1847. The park aims to bring more public green spaces in the city that can help to minimize the impact of industrialization. The park is becoming very popular for its greenery, recreation activities and a place for solitude. Soon, the idea of urban park was being imitated in other cities around the world. Nevertheless, there are parks that are underutilized or not being used. Malaysia, as a country that started to look into the development of urban park more seriously since 1996, also faces the same issue. Using Taman Tasik Seremban as a site study, 196 park users have been surveyed regarding their needs and preferences for park usability. The survey participants were asked to rate how much they prefer to engage in 35 items related to park activities and from factor analysis, five usability dimensions emerged. They are named passive observation and contemplation, passive observation and socializing, exploration, physical activities and family activities. Ranking of the dimensions by using the mean scores show that the most preferred dimension or activities is related to families and the least preferred activity s is exploration. The findings suggest that the design of an urban park in Malaysian cities, particularly in Seremban, should focus more on providing facilities to the family and social activities rather than individual facilities.